Tick-borne encephalitis virus seroprevalence and infection incidence in Switzerland, 2020–2021 - Brêchet, Arthur; Kohler, Philipp; Dörr, Tamara; Grässli, Fabian; Vock, Michael; Salát, Jiří; Růžek, Daniel; Friedl, Andrée; Vuichard-Gysin, Danielle; Croxatto, Antony; Lienhard, Reto; Ackermann-Gäumann, Rahel (Scientific reports, 2025)
Tick-borne encephalitis virus (TBEV) infection can manifest as disease of variable severity, ranging from subclinical infection to severe disease with neurological involvement and potentially fatal outcome. Although TBE is recognized as a major public health problem in Europe, the true burden of disease is potentially underestimated. Here, we investigated TBEV-specific antibody prevalence, infection incidence, and seroreversion and antibody decline rates in a prospective Swiss healthcare worker (HCW) cohort. We screened serum samples from 1444 HCWs between June and October 2020, and from a subset again between August and September 2021, using a TBEV envelope (E) protein IgG ELISA. Positive samples underwent further analysis with a TBEV non-structural protein 1 (NS1) IgG ELISA, and seroconversions in unvaccinated individuals were confirmed by seroneutralization testing. Questionnaire data were used to determine vaccination status and risk factors. TBEV E protein-specific IgG prevalence was 72.1% (95% CI 68.2–75.7%) in TBEV-vaccinated and 6% (95% CI 4.4–7.8%) in unvaccinated individuals. The estimated annual incidence of infection was 735/100,000. Age was the only factor significantly associated with seroprevalence. The seroreversion rate in unvaccinated individuals was 30.3% within one year, which is almost ten times higher than in vaccinated individuals (3.4%, annual decline rate 8.0%). NS1-specific IgG antibodies were six times more common in vaccinated than unvaccinated HCWs. In conclusion, undetected TBEV infections are common, and infection incidence is much higher than reported clinical cases. Individuals with abortive infections have high antibody decline and seroreversion rates. Whether lifelong protection is conferred and by which immune subsets remain unclear.